(untitled) (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2024)
Epilepsy is a neurological condition characterized by recurrent electrical activity in the brain’s temporal lobe. It is a chronic disorder marked by an imbalance between excitatory and inhibitory neurotransmitters, resulting in uncontrolled excitability. Current antiepileptic drugs often have limited effectiveness and pose challenges in patient management. Literature surveys indicate that various species of Elaeocarpus have demonstrated antimicrobial, antioxidant, antidiabetic, antiasthmatic, antihypertensive, and antidepressant properties. Since Rudraksha (Elaeocarpus angustifolius Blume) is traditionally used to treat epilepsy and other brain-related disorders, the present study aimed to validate this claim by evaluating the anti-epileptic activity of the ethanolic bark extract of E. angustifolius on picrotoxin-induced convulsive rats. The extract at doses of 200 and 400 mg/kg BW was administered to rats for 14 days, followed by a single dose of picrotoxin (7.5 mg/kg i.p.) on the 14th day, with diazepam (12 mg/kg i.p.) used as a reference drug. Various oxidative parameters such as γ-aminobutyric acid (GABA), lactoperoxidase (LPO), superoxide dismutase (SOD), glutathione (GSH), and nitrate were estimated at the end of the treatment period. In the picrotoxin-induced convulsion model, treatment with ethanolic bark extract at 400 mg/kg caused a significant (p <0.01) decrease in LPO levels and a significant (p <0.001) increase in GABA levels in epileptic rats. The results concluded that the extract at a 400 mg/kg dose showed the most significant effect on picrotoxin-induced convulsions in rats.